Legacy Collection : Creature from the Black Lagoon - Arnold, Jack, 1916-1992.; Sherwood, John, 1903-1959.; Carlson, Richard, 1912-1977.; Adams, Julie, 1926-2019.; Agar, John, 1921-2002.; Universal Studios Home Entertainment (Firm) (Universal City, CA Universal Studios Home Entertainment, 2014)
Members of a scientific expedition to the Amazon discover a gruesome creature that is half-man and half-fish; "Gill Man" is captured and transported from his Amazon home to a Florida marine park aquarium, where he develops a relationship with a female researcher; despite the clear intention of enjoying his watery home deep in the Everglades, the Creature from the Black Lagoon is disturbed by inquisitive doctors who decide that he would be better off if he were able to walk among men.
Creature from the Black Lagoon (1954) / written by Harry Essex, Arthur A. Ross ; directed by Jack Arnold
Features: Back to the Black Lagoon, commentaries, production photographs, theatrical trailers.
Creature from the Black Lagoon: Richard Carlson, Julia Adams, Richard Denning
Originally released as motion pictures 1954-1956.
MPAA rating: Not rated.
Closed-captioned.
108895
Keywords: Monsters -- Amazon River -- Drama; Scientists -- Drama; Amazon River; Video recordings; Horror films; Feature films; Fiction films; Video recordings for the hearing impaired; Drama